2022
DOI: 10.1002/hed.27083
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelial carcinoma of the parotid gland: Clinicopathological analysis of 146 cases from a single institute

Abstract: BackgroundParotid lymphoepithelial carcinoma (LEC) is a rare malignant tumor. The purpose of this study was to investigate the clinicopathological features of parotid LEC.MethodsAll patients clinicopathological information diagnosed parotid LEC from 2005 to 2017 were analyzed.ResultsA total of 146 cases of parotid LECs were identified. Of these, 126 (86.3%) were primary and 20 (13.7%) were secondary LECs. Patients with secondary LEC tended to have tumors with earlier TNM staging than those with primary (p = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Iezzoni et al reported that there is a consistent association with EBV in salivary gland LEC whereas there is no association in other anatomic sites [ 8 ]. Parotid LECs have more than 90% association with EBV [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iezzoni et al reported that there is a consistent association with EBV in salivary gland LEC whereas there is no association in other anatomic sites [ 8 ]. Parotid LECs have more than 90% association with EBV [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike nonsebaceous lymphadenoma, lymphoepithelial carcinoma is composed only of lymphoepithelial cells, while tubuloglandular components have not been reported. 2,8,9 Nonsebaceous lymphadenoma shows no or very few mitotic figures, and lymphoepithelial carcinoma often shows marked cellular atypia and brisk mitotic activity. Computed tomography may also be helpful in the differential diagnosis, as cervical lymph node metastasis occurs in approximately half of lymphoepithelial carcinoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoepithelial carcinoma is another rare entity and is commonly found in the nasopharynx, parotid gland, larynx, and hypopharynx. 23 , 24 The reported 5-year survival for parotid gland lymphoepithelial carcinoma is 97.0% while that for laryngeal and hypopharynx carcinoma is 68.9%. 23 , 24 The reported prevalence of lymph node metastasis at the time of parotid gland lymphoepithelial carcinoma diagnosis is 31.5%.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 The reported 5-year survival for parotid gland lymphoepithelial carcinoma is 97.0% while that for laryngeal and hypopharynx carcinoma is 68.9%. 23 , 24 The reported prevalence of lymph node metastasis at the time of parotid gland lymphoepithelial carcinoma diagnosis is 31.5%. 23 We also found lymph node metastasis at the time of presentation in children with parotid gland lymphoepithelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%